The social construction of the working day in Chile: absenteeism, delays and workers management of working time in factories (1930-1940); La construcción social de la jornada de trabajo en Chile: ausentismo, atrasos y gestión obrera del tiempo de trabajo en las fábricas (1930-1940)* - Venegas-Valdebenito, H; Morales-Barrientos, D (Universidad de Concepcion, 2025)
Factories need to maximize the performance of workers labor and to this end seek to standardize work systems. However, this was a desire rather than a reality in factories during the first stage of industrialization in Chile. Absenteeism, tardiness and intermittency in the rhythm of work during the working day were regular practices of the workers, who imposed restrictions on the discipline of industrial capital. From this, it is suggested that in the 1930s and 1940s there was an undirected conflict between workers and employers, based on relative degrees of workers autonomy to manage the way in which they executed their productive tasks. © 2025, Universidad de Concepcion. All rights reserved.